Geochemical Characteristics of Trace Elements and REEs and their Geological Significance for Uranium Mineralization within the Qianjiadian Sandstone-Hosted Uranium Deposit, Songliao Basin. (20th April 2023) - Yan, Zhaobin; Ji, Hongjie; Guo, Guolin; Xia, Fei; Zhang, Wenwen; Song, Saisai; Liu, Shaofang
Abstract : The Qianjiadian uranium deposit is a typical interstratified oxidized zone sandstone-hosted uranium deposit hosted in the Upper Cretaceous Yaojia Formation of the southern Songliao Basin. Despite its significance, little research has been conducted on the relationship between trace elements, REEs, and uranium mineralization in this deposit. This study presents new geochemical data from sandstones in the oxidation, transition, and reduction zones. The sandstones in the transition zone are highly enriched in U and moderately enriched in Mo, Cd, and V compared to those in the oxidation and reduction zones. They are also weakly enriched in Co, Ni, and Zn. The oxidation and transition zone sandstones have higher ∑LREE and ∑HREE contents than those in the reduction zone. However, the oxidation zone sandstones are characterized by LREE enrichment and flat HRRE distribution, while the transition zone sandstones show HRRE enrichment and flat LREE distribution. These trace element and REE differentiation characteristics within each subzone are closely related to the geological process of interstratified oxygenation. Oxygenated uranium-bearing fluids from southwestern provenance areas carried multiple trace elements and REEs and infiltrated along the oxidation sandstones to reach the Yaojia Formation's transition zone. During this process, a certain amount of Mo, V, Cd, and LREE from the oxygenated ore-forming fluids was precipitated by Fe-Mn hydroxide adsorption or calcite and siderite cementation. Meanwhile, about 20.33% of preexisting U in the oxidation zone sandstones was continuously extracted and entered into the oxygenated ore-forming fluids. In the transition zone, where dissolved oxygen was exhausted and hydrocarbons were continuously injected, U, Mo, Cd, V, Co, Ni, Zn, and REEs were unloaded and precipitated as uranium minerals, sulfide minerals, or carbonate minerals. The enrichment of Mo, Cd, V, and HREEs in the sandstones can serve as new prospecting indicators for the Qianjiadian uranium deposit.